Anti-heat stress lick block supplementation alleviated the detrimental effects of heat stress on dairy cows - Duan, Hongwei; Zhang, Jiyou; Li, Na; Chen, Liuping; Chen, Danhong; Yang, Hang; Dai, Qiuxia; Shen, Junshi; Mao, Shengyong (Frontiers in Veterinary Science, 2025)
IntroductionHeat stress poses a significant challenge to the development of dairy industry, affecting cows’ well-being and overall productivity, leading to substantial economic losses. In this study, the impact of a specifically formulated anti-heat stress lick block supplement on milk production, milk quality, feed intake, rectal temperature, respiratory rate, and rumen fermentation in cows exposed to heat-stress was evaluated.MethodsTwenty-four healthy Holstein lactating dairy cows were divided into two blocks based on milk yield (low and high), Parity (2–3 parity), and lactation days (114 ± 8 d). The cows in each block were randomly assigned to either a control group without lick block supplementation or a treatment group receiving lick block. The trial lasted for 6 weeks, including a 2-week adaptation phase followed by 4 weeks of feeding treatment.ResultsHeat stress levels varied from severe (THI > 88) to moderate heat stress (THI > 80) in the first 2 weeks, gradually decreasing to mild heat stress (THI > 72) in the following weeks. With the decrease in heat stress, dry matter intake (DMI) and milk production increased (Week: p < 0.05), the rectal temperature and respiratory rate of cows decreased (Week: p < 0.05). Lick block supplementation tended to increase DMI (p = 0.09), and improved milk yield (p < 0.05) without affecting (p > 0.05) milk composition, leading to increased milk yields of fat, protein, and lactose (p < 0.05). Although the overall rectal temperature of cows in the lick block group did not differ from the control group (p > 0.05), the respiratory rate of cows in the lick block group significantly decreased (p < 0.05) in the second and third weeks. Supplementation with the lick block increased (p < 0.05) rumen pH and decreased (p < 0.05) NH3-N and propionate concentrations in dairy cows, and tended to lower the acetate-to-propionate ratio (p = 0.07), total VFA concentration (p = 0.07), and butyrate concentration (p = 0.09).ConclusionSupplementation of anti-heat stress lick block alleviated the detrimental effects of heat stress on dairy cows within a certain range of temperature and humidity.